Pooled safety analysis of tisagenlecleucel in children and young adults with B cell acute lymphoblastic leukemia. Issue 8 (5th August 2021) - Levine, John E; Grupp, Stephan A; Pulsipher, Michael A; Dietz, Andrew C; Rives, Susana; Myers, G Douglas; August, Keith J; Verneris, Michael R; Buechner, Jochen; Laetsch, Theodore W; Bittencourt, Henrique; Baruchel, Andre; et al.
Abstract : Background: Tisagenlecleucel, an anti-CD19 chimeric antigen receptor T cell therapy, has demonstrated efficacy in children and young adults with relapsed/refractory B cell acute lymphoblastic leukemia (B-ALL) in two multicenter phase 2 trials (ClinicalTrials.gov, NCT02435849 (ELIANA) and NCT02228096 (ENSIGN)), leading to commercialization of tisagenlecleucel for the treatment of patients up to age 25 years with B-ALL that is refractory or in second or greater relapse. Methods: A pooled analysis of 137 patients from these trials (ELIANA: n=79; ENSIGN: n=58) was performed to provide a comprehensive safety profile for tisagenlecleucel. Results: Grade 3/4 tisagenlecleucel-related adverse events (AEs) were reported in 77% of patients. Specific AEs of interest that occurred ≤8 weeks postinfusion included cytokine-release syndrome (CRS; 79% (grade 4: 22%)), infections (42%; grade 3/4: 19%), prolonged (not resolved by day 28) cytopenias (40%; grade 3/4: 34%), neurologic events (36%; grade 3: 10%; no grade 4 events), and tumor lysis syndrome (4%; all grade 3). Treatment for CRS included tocilizumab (40%) and corticosteroids (23%). The frequency of neurologic events increased with CRS severity (p<0.001). Median time to resolution of grade 3/4 cytopenias to grade ≤2 was 2.0 (95% CI 1.87 to 2.23) months for neutropenia, 2.4 (95% CI 1.97 to 3.68) months for lymphopenia, 2.0 (95% CI 1.87 to 2.27) months for leukopenia, 1.9 (95% CI 1.74 to 2.10) months for thrombocytopenia, and 1.0 (95% CI 0.95 to 1.87) month for anemia. All patients who achieved complete remission (CR)/CR with incomplete hematologic recovery experienced B cell aplasia; however, as nearly all responders also received immunoglobulin replacement, few grade 3/4 infections occurred >1 year postinfusion. Conclusions: This pooled analysis provides a detailed safety profile for tisagenlecleucel during the course of clinical trials, and AE management guidance, with a longer follow-up duration compared with previous reports.